Strategi Pengembangan Sub Terminal Agribisnis Komoditi Mentimun di Kelurahan Koto Baru Payo Basuang Kecamatan Payakumbuh Timur - Ziret Nengsih; Husnarti Husnarti; Revi Ernanda (CULTIVATE: Journal of Agriculture Science, 2025)
The mechanism of the agribusiness sub-terminal is to collect agricultural production from the agribusiness subterminal and partner farmers then from traders who pre-order by telephone through the agribusiness sub-terminal administrator. The highest bid will receive agricultural products. According to Tanjung (2018), STA is a marketing infrastructure located in production centers as a place to buy and sell agricultural products, related to physical and non-physical trade, so that the focus of STA becomes a marketing space carried out by central producers. This study aims to first determine the internal and external environmental factors that influence STA Koba Jaya in Koto Baru Payo Basuang Village, and secondly to determine the development strategy of STA Koba Jaya in Koto Baru Payo Basuang Village. This study was conducted from July to September 2023. The research method used is quantitative descriptive. The data analysis technique uses the EFAS IFAS and SWOT matrices. The results of this study indicate that the internal factors that influence STA cucumber commodities are: product quality, price information, perishable products, financial conditions and lack of operational vehicles. External factors affecting STA Koba Jaya cucumber commodity: market share, number of collectors, fluctuating product prices, government support and promotion. Based on the SWOT analysis for the STA development strategy, the W-O strategy is prioritized, namely utilizing government support to complete STA Koba Jaya facilities, using product marketing on social media, increasing loyal customers and maximizing planting pattern strategies to stabilize product supply so that consumer demand is met.